Chemical, Mechanical, and Heat Cleaning to Decontaminate Hospital Drains Harboring Carbapenemase-Producing Enterobacteriales. (October 2020) - Jamal, Alainna Juliette; Pantelidis, Rajni; Sawicki, Rachael; Li, Angel; Chiu, Wayne; Morrison, Deborah; Marshman, John; Baqi, Mahin; Richardson, David; McGeer, Allison; Borgia, Sergio
Abstract : Background: Carbapenemase-producing Enterobacteriales (CPE) outbreaks have been linked to contaminated wastewater drainage systems in hospitals. The optimal strategy for CPE decontamination of drains is unknown. In this randomized controlled trial, we aimed to determine whether combining chemical, mechanical, and heat cleaning was superior to routine cleaning for drain decontamination. Methods: We enrolled CPE-contaminated hospital drains at 2 geographic locations. Eligible drains were those initially found to be culture positive in a 2017 study and that remained positive (by RT-PCR) when retested twice in August 2018. Drains were stratified by type (sink versus shower) and randomized with a 1:1 allocation ratio (as per computer-generated randomization) to standard-of-care cleaning (comparator) or combined chemical, mechanical, and heat cleaning (intervention) on day 0. Drain tail pieces were swabbed on days 0 (before administration of the intervention), 1, 2, 3, 7, and 14, and at months 1, 2, 3, 4, 5, and 6. Swabs were placed into brain heart infusion with 10% Dey-Engley neutralizing broth and incubated overnight. Direct RT-PCR was performed to detect KPC, VIM, NDM, OXA-48–like, IMP, GES, and SME genes. The primary outcome was drain decontamination, defined as no detectable carbapenemase gene in the drain from day 1 to 7 (inclusive). Results: Overall, 33 CPE-contaminated drains were enrolled (7 sink and 26 shower); 17 and 16 drains were randomized to the intervention and comparator, respectively. Moreover, 12 (36%) drains met the primary outcome of decontamination, 18 (55%) remained contaminated, and 3 (9%) could not be assessed. Among drains that could be assessed, 11 of 15 (74%) in the intervention group met the primary outcome of decontamination compared to 1 of 15 (7%) in the comparator group ( P = .0005). Of the 11 drains in the intervention group that were decontaminated, the carbapenemase gene present at enrollment was subsequently detected in 10 (91%): 1 (10%) at day 14, 3 (30%) at month 1, 4 (40%) at month 3, 1 (10%) at month 4, and 1 (10%) at month 6. The median time to a swab yielding CPE was 1 day in the comparator group versus 14 days in the intervention group (Fig. 1). Overall, 24 drains (73%) had a carbapenemase gene (that was not detectable at enrollment) appear in the follow-up. Of patients identified as CPE colonized or infected during this study, none occupied rooms with these drains. Conclusions: Chemical, mechanical, and heat cleaning were superior to standard cleaning for CPE decontamination of hospital drains at 7 days, but these trends were not sustained. Such cleaning may be useful if applied repeatedly. Funding: None Disclosures: Allison McGeer reports funds to her institution for studies for which she is the principal investigator from Pfizer and Merck as well as consulting fees from Sanofi-Pasteur, Sunovion, GSK, Pfizer, and Cidara.